High-throughput evaluation of hemolytic activity through precise measurement of colony and hemolytic zone sizes of engineered Bacillus subtilis on blood agar - Bamba, Takahiro; Aoki, Rina; Hori, Yoshimi; Ishikawa, Shu; Yoshida, Ken-ichi; Taoka, Naoaki; Kobayashi, Shingo; Yasueda, Hisashi; Kondo, Akihiko; Hasunuma, Tomohisa (Biology Methods and Protocols, 2024)
Biosurfactants have remarkable characteristics, such as environmental friendliness, high safety, and excellent biodegradability. Surfactin is one of the best-known biosurfactants produced by Bacillus subtilis. Because the biosynthetic pathways of biosurfactants, such as surfactin, are complex, mutagenesis is a useful alternative to typical metabolic engineering approaches for developing high-yield strains. Therefore, there is a need for high-throughput and accurate screening methods for high-yield strains derived from mutant libraries. The blood agar lysis method, which takes advantage of the hemolytic activity of biosurfactants, is one way of determining their concentration. This method includes inoculating microbial cells onto blood-containing agar plates, and biosurfactant production is assessed based on the size of the hemolytic zone formed around each colony. Challenges with the blood agar lysis method include low experimental reproducibility and a lack of established protocols for high-throughput screening. Therefore, in this study, we investigated the effects of the inoculation procedure and media composition on the formation of hemolytic zones. We also developed a workflow to evaluate the number of colonies using robotics. The results revealed that by arranging colonies at appropriate intervals and measuring the areas of colonies and hemolytic rings using image analysis software, it was possible to accurately compare the hemolytic activity among several colonies. Although the use of the blood agar lysis method for screening is limited to surfactants exhibiting hemolytic activity, it is believed that by considering the insights gained from this study, it can contribute to the accurate screening of strains with high productivity.